86 Direct-to-Consumer vs. Traditional Prescriptions of PDE5 inhibitors: A Contemporary Cost-Analysis. Issue 1 (1st April 2022) - Schneider, D; Loeb, C; el-Khatib, F; Jenkins, L; Yafi, F
ABSTRACT: Introduction: After a text screen and focused telehealth visit, patients can now have access to phosphodiesterase inhibitor (PDEi) prescriptions through online direct to consumer (DTC) healthcare companies. Prescription of PDEis has unknown costs relative to the traditional office visit, especially with the availability of online discounts. Objective: This study seeks to quantify the cost of DTC PDEi treatment compared to a traditional physician visit and local pharmacy prescription fulfillment. Methods: Nine pharmacies were included, including two DTC companies, two compounding pharmacies with national reach, three online Canadian pharmacies licensed by the Canadian International Pharmacy Association, and sixteen American pharmacy chains, representing all locally available chains. National pharmacies which are subsidiaries were grouped together. Prices for chains were determined using their publicly available price on GoodRx® with coupons in Irvine, CA (92612), Cleveland, OH (44101), New York, NY (10001), Dallas, TX (75201), and Birmingham, AL (35201). Cost of physician visit was determined using 2020 CMS reimbursement for a level 3 new patient visit. Prices for DTC companies were acquired from direct communication with the company. Where offerings did not align with 90 dose regimens, price per pill was determined and price for 90 doses was calculated. Results: For a 90-dose supply of sildenafil 20mg, a physician visit and local prescription cost a mean of $191.51 with a low of $125.45, compounding pharmacy prescription cost a mean of $218.28 with a low of $144.35, and Canadian pharmacy prescription cost a mean of $240.25 with a low of $169.34, compared to a mean of $220.00 and a low of $180.00 for online DTC. For sildenafil 100mg, a physician visit and local prescription had a mean cost of $524.11 with a low cost of $137.16, compounding pharmacy prescription a mean cost of $401.78 with a low cost of $289.35, and Canadian pharmacy prescription a mean cost of $262.63 with a low cost of $200.36, compared to a mean and low cost of $900.00 for DTC. For tadalafil 5mg, a physician visit and local prescription cost a mean of $205.79 with a low of $125.80, compounding pharmacy prescription cost a mean of $179.33 with a low of $169.35, and "Canadian" pharmacy prescription cost a mean of $207.59 with a low of $195.34, compared to an average and low of $720.00 for DTC. Finally, for tadalafil 20mg, a physician visit and local prescription cost a mean of $643.70 with a low of $161.00, compounding pharmacy prescription cost a mean of $359.33 with a low of $289.35, and Canadian pharmacy prescription cost a mean of $291.74 with a low of $229.00, compared to a mean of $3420.00 and a low of $2880.00 for DTC (Table 1). Conclusions: Our findings suggest that local pharmacies, in conjunction with online coupons, consistently provide a markedly less expensive option for fulfillment of PDEi prescriptions than online DTC services, compounding, or Canadian pharmacies, in addition to the established benefits of physician visits for screening. This is most pronounced if patients have flexibility in where they fill their prescriptions and can use the available local prices. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: FY: Coloplast (consultant), Cynosure (consultant) LJ: Hims (consultant)